Etnodesign: a produção artesanal como fonte de conhecimento histórico e a sua contribuição socioambiental - Pizzolatto, Cléo Medeiros (My University, 2023)
The dissertation to be presented deals, through research, with an excerpt about the term Ethnodesign, comprising crafts and artisanal production as a source of historical knowledge. It is argued here that a product made from the creativity of artisans from different communities generates cultural and economic values - and carries the skill of the practices and knowledge transmitted from generation to generation, in addition to contributing to the socio-environmental aspect, since the techniques applied in its production use materials that are not harmful to nature, making manual work an ally in reducing waste. To this end, topics such as intangible heritage, sustainable practices, circular and creative economy and the very relationship "consumer versus consumerism" established from the Industrial Revolution in the 19th century onwards are addressed, including the factor of planned obsolescence as a generator of disposal in production in mechanized series. The objective was to demonstrate, through research data, the contribution of Etnodesign - a mediator between the knowledge of designers and the knowledge of artisans - both culturally and in reducing the negative impact on the environment, making products potentially objects of socio-environmental transformation. Authors such as Roger Chartier, Clifford Geertz and Jacques Le Goff based the considerations on cultural history, representations, memory and intangible heritage. William McDonough, Catherine Weetman and Lia Krucken were used to support the discussion on circular economy, sustainable practices and design.In addition to the documentary research and the theoretical references used, an interview was conducted with the designer and craftsman from Ceará, Elizandro Rabelo, in order to understand his manual work technique in the production of handcrafted pieces and the circular economy model implemented in his studio, and a practical example of Ethnodesign was also demonstrated, through the project by São Paulo designer Marcelo Rosenbaum, together with the Yawanawás indigenous community, to create a collection of lamps entitled "A Força da Floresta". As a result of this dissertation, a workshop entitled "Knowledge and Actions: a look at Heritage Education" was held with fifth-year students from a school in Caxias do Sul, and a project named "Podcast as an Educational Tool" was formalized. , applied to a community that produces handicrafts, in order to become a resource for educators to work on Ethnodesign issues. The result of this study was achieved by demonstrating that handicrafts made from artisanal knowledge carry inherited ancestral knowledge and are a source of great cultural potential, which preserves identities, generates immaterial and economic values for communities, causes social transformations and contributes to environmental preservation in all its phases, creation, production and disposal. [resumo fornecido pelo autor]
A dissertação a ser apresentada trata, através de pesquisa, de um recorte acerca do termo Etnodesign, compreendendo o artesanato e a produção artesanal como fonte de conhecimento histórico. Defende-se, aqui, que produto feito a partir da criatividade de artesãos de diversas comunidades gera valores culturais e econômicos e carrega a habilidade dos fazeres e dos saberes transmitidos de geração a geração, além de contribuir com o aspecto socioambiental, uma vez que as técnicas aplicadas na sua produção utilizam-se de materiais não agressivos à natureza, fazendo do trabalho manual um aliado na diminuição de resíduos. Para tanto, abordam-se temas como patrimônio imaterial, práticas sustentáveis, economia circular e criativa e a própria relação "consumidor versus consumismo" estabelecida a partir da Revolução Industrial no século XIX, incluindo o fator da obsolescência programada como geradora de descarte na produção em série mecanizada. O objetivo foi demonstrar, através de dados da pesquisa, a contribuição do Etnodesign - um mediador entre o conhecimento de designers e o conhecimento de artesãos - tanto culturalmente quanto na diminuição do impacto negativo ao meio ambiente, tornando os produtos potencialmente objetos de transformação socioambiental. Autores como Roger Chartier, Clifford Geertz e Jacques Le Goff embasaram as considerações sobre história cultural, representações, memória e patrimônio imaterial. William McDonough, Catherine Weetman e Lia Krucken foram utilizados para como suporte à discussão sobre economia circular, práticas sustentáveis e design. Além da pesquisa documental e dos referenciais teóricos utilizados, foi realizada uma entrevista com o designer e artesão cearense, Elizandro Rabelo, a fim de compreender a sua técnica de trabalho manual na produção de peças artesanais e o modelo de economia circular implantado em seu ateliê, e também foi demonstrado um exemplo prático de Etnodesign, por meio do projeto do designer paulistano Marcelo Rosenbaum em conjunto com a comunidade indígena Yawanawás, de realização da coleção de luminárias intitulada "A Força da Floresta". Como produto desta dissertação, foi realizada uma oficina, intitulada "Saberes e Fazeres: um olhar sobre a Educação Patrimonial", com os estudantes do quinto ano de uma escola de Caxias do Sul, e formalizado um projeto de nome "Podcast como Ferramenta Educacional", aplicado junto a uma comunidade que produz artesanato, a fim de se tornar um recurso aos educadores para trabalhar questões de Etnodesign. O resultado deste estudo foi atingido, ao demonstrar que as peças manuais feitas a partir de saberes artesanais carregam conhecimentos ancestrais herdados e são fonte de grande potencial cultural, que preserva identidades, gera valores imateriais e econômicos para as comunidades, provoca transformações sociais e contribui com a preservação ambiental em todas as suas fases, de criação, produção e descarte. [resumo fornecido pelo autor]
Keywords: Artesanato - História; Artesanato - Aspectos sociais; Design; Economia circular; Patrimônio cultural - Aspectos ambientais; Handicraft - History; Handicraft - Social aspects; Circular economy; Cultural property - Environmental aspects